Central Java Election Supervisory Agency Strategies for Preventing Violations during Indonesia’s 2024 Regional Elections - Muhammad Arsy Haryanto; Puji Lestari (Universitas Negeri Semarang, 2025)
The high incidence of electoral violations during Indonesia’s 2019 General Election and the 2024 Regional Head Elections has raised significant concerns for the Central Java Election Supervisory Agency (Bawaslu) in strengthening preventive electoral oversight. This study aims to analyze the strategies employed by the agency to prevent electoral violations during Indonesia’s 2024 Regional Elections using G. R. Terry’s strategic management theory as the analytical framework. A descriptive qualitative approach was employed, with data collected through in-depth interviews and document analysis. The findings indicate that the agency implemented four major preventive strategies: strengthening political education and public outreach, promoting participatory electoral supervision, enhancing coordination with relevant stakeholders, and leveraging information technology to improve monitoring effectiveness. Nevertheless, these strategies encountered several challenges, including limited political literacy, inadequate human resources, low public reporting awareness, and budget constraints. The study concludes that these preventive strategies have strengthened electoral governance and contributed to mitigating potential electoral violations, although greater institutional support and innovation in participatory supervision remain essential for improving electoral integrity in future regional elections.